La reforma neocolonial de la plaza de Armas. Modernización urbana y patrimonio arquitectónico en Lima, 1901-1952 - Ramos, Horacio (2016)
This essay illustrates how the debates surrounding the neo-colonial redevelopmentof Lima’s Plaza de Armas (1940-1952) altered perceptions of the city’s urban modernization and architectural heritage. Analyzing projects dating back to the turn of the 20th century reveals that the redevelopment was part of a series ofurban interventions involving the destruction of architectural heritage and the construction of major avenues and buildings. The promoters of functionalismcriticized the redevelopment, causing this type of urban intervention and the neo-colonial style as «anachronistic».